Evaluation of Convective Heat Transfer and Natural Circulation in an Evacuated Tube Solar Collector (Journal of Engineering, 2013)
The evacuated tube solar collector ETC is studied intensively and extensively by experimental andtheoretical works, in order to investigate its performance and enhancement of heat transfer, for Baghdad climatefrom April 2011 till the end of March 2012. Experimental work is carried out on a well instrumented collectorconsists of 16 evacuated tubes of aspect ratio 38.6 and thermally insulated tank of volume 112L. The relationbetween convective heat transfer and natural circulation inside the tube is estimated, collector efficiency, effect oftube tilt angles, incidence angle modifier, The solar heating system is investigated under different loads pattern (i.eclosed and open flow) to evaluate the heat loss coefficient from tank and tubes, test the collector with variousaspect ratios (32.9 and 27.2). The enhancement in collector performance is studied by using two reflectors (FlatPlate and Curved Plate) and nanofluid (Water-AL2O3).Theoretical work is run by software (Fluent 6.3), to computethe velocity and temperature profiles within the tube, for different tube diameters, effect of tube junction angle andstagnant region in the bottom of the evacuated tube. The experimental results shows that the heat loss coefficientfor tube is W/m2.K and for tank is W/m2.K, the maximum collector temperature is 79°C in winter and99°C in summer, while that belong to nanofluid collector is 99°C in winter. The best tilted angle (optimum) ofevacuated tube is 41° annually. The collector efficiency increased when using nanofluid of (1, 0.6, 0.3)% volumefraction as(28.4, 6.8, 0.6)% respectively. The efficiency decreases as (33, 62)% when decreasing tube aspect ratiofrom 38.6% to 32.9% and 27.2% respectively. An increase of (16.9 and 7.08)% in collector efficiency is obtainedwhen using curved and flat plate reflectors respectively. From simulation the best junction angle of the tank is22.5°. The stagnant region is influenced with changing heat flux, tilted angle and aspect ratio.